Frontal Sinus Cyst Surgery Complicated by Central Retinal Artery Occlusion - Ota Yasushi (Journal of Otolaryngology Advances, 2016)
Central retinal artery occlusion (CRAO) is a retinal ischemic disorder associated with sudden loss of vision and has a poor prognosis. We report a case of CRAO that occurred during frontal sinus surgery involving craniotomy in a patient with a frontal sinus cyst. The prognosis for treatment after the acute phase is generally unfavorable; however, aggressive treatment is recommended for patients with visual acuity of “hand motion” or better within 1 day after onset. This case highlights the need for informed consent prior to nasal or paranasal sinus surgery, including mention of the possibility of CRAO as a complication.
Keywords: CT